Elevated D-dimer level is an independent risk factor for cardiovascular death in out-patients with symptoms compatible with heart failure - Alehagen, Urban; Dahlström, Ulf; Lindahl, Tomas L. (Thrombosis and Haemostasis, 2004)
D-dimer, a marker of fibrin turnover, exhibits many interesting properties as a biological marker of thrombosis. Some of the properties of D-dimer might also be used to provide additional information about patients with heart failure. In this study, we evaluate the prognostic information acquired from D-dimer concerning increased risk of cardiovascular mortality in an elderly population with symptoms associated with heart failure. A cardiologist examined 458 elderly patients, out of 548 invited, attending primary care for symptoms of dyspnoea, fatigue and/or peripheral oedema and assessed NYHA functional class and cardiac function. Abnormal systolic function was defined as EF <40% on Doppler echocardiography. Abnormal diastolic function was defined as reduced E/A ratio and/or an abnormal pattern of pulmonary venous flow. Blood samples were drawn, and BNP and D-dimer were analysed. D-dimer was analysed using an automated micro-latex assay. A statistical analysis was performed to identify the prognostic value of increased plasma concentration of D-dimer. Results showed that during a median follow-up period of 5.5 years, 68 (14%) patients died of cardiovascular disease. No gender difference was noted. A plasma concentration of D-dimer >0.25mg/L increased the risk almost 4-fold. In conclusion, D-dimer is an independent risk factor for cardiovascular mortality that may be used to risk-stratify patients with heart failure.
Keywords: Heart failure; elderly patients; primary health care; D-dimer; prognosis